ISSUES OF DEVELOPING "GREEN" FINANCE IN UZBEKISTAN - DSc Abdurakhimova Dilora Karimovna (American Journals, 2024)
The article analyzes the problems and prospects for the development of "green" financing in Uzbekistan, which is an important tool for sustainable economic growth and environmental protection. In the context of global environmental challenges and Uzbekistan's desire to modernize its economy, the introduction of green financial mechanisms is becoming a key factor in achieving sustainable development. The article discusses the main problems the country faces in introducing green financing, such as insufficient institutional support, limited knowledge and experience in the field of ecology and financing of "green" projects, as well as the need to change legislative and regulatory mechanisms.
Keywords: Green finance; sustainable development; ESG; green budgeting; green financial instruments; climate risks; financial market; payments for natural resources.